2017
DOI: 10.1038/cddis.2017.450
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the deubiquitinase USP5 leads to c-Maf protein degradation and myeloma cell apoptosis

Abstract: The deubiquitinase USP5 stabilizes c-Maf, a key transcription factor in multiple myeloma (MM), but the mechanisms and significance are unclear. In the present study, USP5 was found to interact with c-Maf and prevented it from degradation by decreasing its polyubiquitination level. Specifically, the 308th and 347th lysine residues in c-Maf were critical for USP5-mediated deubiquitination and stability. There are five key domains in the USP5 protein and subsequent studies revealed that the cryptic ZnF domain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 23 publications
0
87
0
Order By: Relevance
“…In breast cancer, TMEPAI promotes breast cancer cell proliferation by converting TGF-β from a tumor suppressor to a tumor promoter (5), while in lung cancer cells, TMEPAI sequestrates R-SMAD and downregulates PTEN therefore enhancing the PI3K/AKT signaling pathway (3). In our present study, TMEPAI-induced MM cell apoptosis is probably associated with c-Maf ubiquitination and degradation because c-Maf promotes MM cell survival while silencing c-Maf leads to MM cell apoptosis (19). Moreover, TMEPAI is markedly downregulated in MM cells but highly expressed in bone marrow cells from healthy donors.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In breast cancer, TMEPAI promotes breast cancer cell proliferation by converting TGF-β from a tumor suppressor to a tumor promoter (5), while in lung cancer cells, TMEPAI sequestrates R-SMAD and downregulates PTEN therefore enhancing the PI3K/AKT signaling pathway (3). In our present study, TMEPAI-induced MM cell apoptosis is probably associated with c-Maf ubiquitination and degradation because c-Maf promotes MM cell survival while silencing c-Maf leads to MM cell apoptosis (19). Moreover, TMEPAI is markedly downregulated in MM cells but highly expressed in bone marrow cells from healthy donors.…”
Section: Discussionmentioning
confidence: 69%
“…Because c-Maf is a transcription factor, we next evaluated to whether TMEPAI modulated c-Maf transcriptional activity. To this end, a luciferase construct directed by MARE (Maf recognition element) (19) was co-transfected with wild-type or ΔTM-TMEPAI. The luciferase activity analysis revealed that ΔTM-TMEPAI lost its modularity on the stability and transcriptional activity of c-Maf (Fig.…”
Section: The Transmembrane Domain Is Indispensable For Tmepai-mediatementioning
confidence: 99%
See 1 more Smart Citation
“…USP5 has been associated with tumorigenesis [15][16][17][18][19] , neurodegeneration [20][21][22] , and viral infections 23,24 . In addition, USP5 plays a role in regulation of ubiquitin levels in DNA damage repair 25 and stress granules 26 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] As a member of the USPs family, USP5 can play the role of deubiquitination enzyme by hydrolyzing ubiquitin chain. 24,25 Wang et al 26 found that inhibiting the expression of deubiquitinase USP5 could lead to degradation of c-Maf protein and induce apoptosis of MM cells. 24,25 Wang et al 26 found that inhibiting the expression of deubiquitinase USP5 could lead to degradation of c-Maf protein and induce apoptosis of MM cells.…”
mentioning
confidence: 99%